OPTIMALISASI PERAN PEMERINTAH DAERAH DALAM PENYELESAIAN KONFLIK PERTANAHAN DI DAERAH SEBAGAI UPAYA PERLINDUNGAN TERHADAP HAK WARGA NEGARA - Tamudin, M. (Universitas Islam Negeri Raden Fatah Palembang, 2018)
Land conflicts in the reform era are increasingly complex and tend to increase in proportion to the community's need for land. Government Regulation Number 38 Year 2007 Concerning the Division of Government Affairs between the Government, Provincial Government and District or City Government, authorizes local governments to mediate mediation in resolving land conflicts in the regions. This authority does not run optimally. There are some obstacles that make this rule impossible to perform optimally. There are several obstacles experienced by the City Government of Palembang in resolving conflicts in the region, among others: No Clarity of Status of City Government In Settlement of Land disputes in the city of Palembang; The absence of Special Events Law which regulates the Settlement of Land Conflict in Palembang City; Absence of Legal Certainty from Legal Products (compromise) produced by both disputing Parties; Not yet the establishment of Special Agencies dealing with land disputes only in the form of a committee consisting of ordinary apparatus; The lack of good faith from the parties to the dispute.